2011
DOI: 10.1007/s00464-011-1952-2
|View full text |Cite
|
Sign up to set email alerts
|

Outcome of laparoscopic colorectal surgery in obese and nonobese patients: a meta-analysis

Abstract: Obesity is associated with increased conversion rate, operating time, and postoperative morbidity of laparoscopic colorectal surgery but does not affect surgical safety or oncological security.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
55
1
1

Year Published

2012
2012
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 77 publications
(61 citation statements)
references
References 34 publications
4
55
1
1
Order By: Relevance
“…Obesity has been also described as a risk factor for surgical wound infection after conventional colorectal surgery [23,24]. Zou et al [25] reported that obesity was associated with increased wound infection, ileus, incisional hernia, and with pulmonary events. The incidence of wound infection seen in obese patients in our study, which was similar to that in other studies [26,27], was significantly higher than that in non-obese patients (8.3% vs 1.9%).…”
Section: Discussionmentioning
confidence: 99%
“…Obesity has been also described as a risk factor for surgical wound infection after conventional colorectal surgery [23,24]. Zou et al [25] reported that obesity was associated with increased wound infection, ileus, incisional hernia, and with pulmonary events. The incidence of wound infection seen in obese patients in our study, which was similar to that in other studies [26,27], was significantly higher than that in non-obese patients (8.3% vs 1.9%).…”
Section: Discussionmentioning
confidence: 99%
“…Zhou et al, en un reciente meta análisis 15 , encontraron un 34,8% de complicaciones en pacientes obesos comparado con un 23,4% en no obesos, especialmente complicaciones como íleo, infección de sitio quirúrgico y eventos pulmonares. Con respecto a filtración, abscesos, hemorragias y mortalidad no encontraron diferencias.…”
Section: Discussionunclassified
“…A striking coefficient is the patient-specific individual anatomy and tumor manifestation: A narrow male pelvis, obesity, and bulky and low tumors can substantially hamper LS [8,9,16,28]. Hence, RS was proposed and has already demonstrated ability to address the problem of anatomical limitations in low anterior resection.…”
Section: Resultsmentioning
confidence: 99%
“…In lower gastrointestinal surgery, the broad implementation of minimally invasive procedures has been substantially hampered by the demanding anatomical and technical complexities of colorectal surgery such as the narrow male pelvis, obesity, locally advanced disease, low rectal masses, or the necessity of intracorporeal ileocolic anastomosis [8,9]. Moreover, certain pitfalls of the laparoscopic approach, such as 2-dimensional vision, tremor, and limitations in triangulation and motility, potentially impede the procedure.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation